2018
DOI: 10.19164/ijcle.v25i3.768
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perceptions of Clinical Legal Education within an employability context

Abstract: <p>The purpose of this paper is to examine how clinical legal education is perceived by current students, alumni, employers and clinic supervisors. The paper considers clinical legal education within the employability discourse in higher education and interrogates its place in the curriculum. With ever growing pressure on Higher Education providers to produce employable graduates in a challenging graduate marketplace this qualitative study seeks new insights into the role clinical legal education can pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…None of the participants identified clinic as developing understanding that a law firm is a business and needs to make money – either by explicitly discussing that or through mentioning any activities that link to this aspect of the definition of commercial awareness. The data appears to align with Alexander and Boothby’s ( 2018 ) finding that CLE must enable students to experience the commercial realities of practice more but contrasts with other viewpoints that argue CLE provides this insight. 67 CLE arguably provides an authentic opportunity to provide practical understanding that a law firm is a business, particularly because in the author’s clinic students work in firms advising clients and recording their time.…”
Section: Findings and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…None of the participants identified clinic as developing understanding that a law firm is a business and needs to make money – either by explicitly discussing that or through mentioning any activities that link to this aspect of the definition of commercial awareness. The data appears to align with Alexander and Boothby’s ( 2018 ) finding that CLE must enable students to experience the commercial realities of practice more but contrasts with other viewpoints that argue CLE provides this insight. 67 CLE arguably provides an authentic opportunity to provide practical understanding that a law firm is a business, particularly because in the author’s clinic students work in firms advising clients and recording their time.…”
Section: Findings and Discussionsupporting
confidence: 80%
“…51 A small-scale international study by Cantatore et al ( 2021 ) identified that pro bono work improved students’ industry awareness, 52 providing them with a better understanding of legal practice and how firms operate. In contrast, a study by Alexander and Boothby ( 2018 ) found that alumni participants working in the legal profession, who had experienced CLE whilst at university, did not feel that clinic had developed their commercial awareness. The authors noted the challenge in providing an authentic experience of the commercial dynamics of practice in a CLE setting.…”
Section: Existing Literature On the Development Of Commercial Awarene...mentioning
confidence: 89%
See 1 more Smart Citation
“…1213 Law schools themselves have made efforts to develop students' employability in their curriculums, often in the form of pro bono law clinics, 14 as they "strive to ensure their students' skill-set meet ever-shifting employer expectations". 15 Great value is placed on employment as a graduate outcome: it is used by the Office for Students and the Department of Education as a performance measure for higher education institutions, including as part of the Teaching Excellence Framework. 16 While there is a debate to be had about the use of these measures and how strongly employment is valued by regulators and government compared with other elements of higher education, students will almost certainly have to seek employment on completing their studies, and in the current political and financial climate it is in institutions' interests to help them do so.…”
Section: Librarians Commercial Awareness and Employabilitymentioning
confidence: 99%
“…Practical work experience during their law degree increases self-confidence, practical experience and consequently, employability. 86 Many students are working alongside their studies, which is a barrier to gaining unpaid legal work experience 87 and some students would not necessarily have the confidence to put themselves forward for work experience 88 . This module gives students the opportunity to undertake work experience within an organisation as part of their degree, thereby allowing them to develop skills and enhance their CVs.…”
Section: Analysis Of the Law In Community Modulementioning
confidence: 99%